Severe hemolysis after plasma transfusion in a neonate with necrotizing enterocolitis, Clostridium perfringens infection, and red blood cell T‐polyagglutination. Issue 11 (22nd June 2017) - Moh‐Klaren, Julia; Bodivit, Gwellaouen; Jugie, Myriam; Chadebech, Philippe; Chevret, Laurent; Mokhtari, Mostafa; Chamillard, Xavier; Gallon, Philippe; Tissières, Pierre; Bierling, Philippe; Djoudi, Rachid; Pirenne, France; et al.
Abstract : BACKGROUND: Red blood cell (RBC) Thomsen‐Friedenreich antigen exposure (T activation) in infants with necrotizing enterocolitis (NEC) has occasionally been associated with posttransfusional intravascular hemolysis thought to be due to anti‐T antibodies in the donor plasma. STUDY DESIGN AND METHODS: We describe an infant with NEC and Clostridium perfringens infection complicated by severe hemolysis after plasma transfusion. After this case, infants with confirmed NEC were prospectively evaluated for T activation. We checked for hemolysis in patients with T activation receiving plasma‐containing blood products. RESULTS: The infant had received 80 mL of fresh‐frozen plasma (FFP). His RBCs displayed strong T activation, and agglutination was observed with four of six ABO‐compatible FFP units. A direct antiglobulin test was negative. IgM‐class anti‐T antibodies were present in small amounts (titer of 8) in the transfused FFP. Anti‐T antibodies from the blood donor were not hemolytic in vitro. In the prospective study, T activation was observed in three of 28 infants with NEC (11%). One infant presented moderate T activation and two infants presented very strong T activation but only moderate decreases in sialic acid expression on the RBC membrane. These three infants presented no signs of hemolysis after transfusion with unwashed blood products or FFP. CONCLUSION: Anti‐T antibodies are unlikely to be the etiologic factor for the hemolytic reactions observed in infants with NEC and T activation. Massive RBC desialylation and the direct action of bacterial toxins are more probable causes. Strict avoidance of plasma‐containing blood products does not seem justified in these infants.